Adaptive neural controller implementation in Autonomous Mini Aircraft Quadrotor (AMAC-Q) for attitude control stabilization - Shaiful, Zairi; Hazry, Desa, Dr. (Universiti Teknologi MARA (UiTM), 2011)
7th International Colloquium on Signal Processing and its Applications (CSPA 2011) organized by Universiti Teknologi MARA (UiTM), 4th - 6th March 2011 at Penang, Malaysia.